2008
DOI: 10.1530/rep-07-0522
|View full text |Cite
|
Sign up to set email alerts
|

Marine fish spermatozoa: racing ephemeral swimmers

Abstract: After a long period of spermatogenesis (several weeks to months), marine fish spermatozoa are delivered at male spawning in seawater (SW) at the same time as ova. In some fish species, as the ova micropyle closes quickly after release, these minute unicells, the spermatozoa, have to accomplish their task of reaching the micropyle within a very brief period (several seconds to minutes), for delivery of the haploid male genetic information to the ova. To achieve this goal, their high-performance motile equipment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
150
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(170 citation statements)
references
References 117 publications
8
150
1
6
Order By: Relevance
“…During spermatogenesis, sperm cells are prepared for accomplishing their fertilizing task for which they need to fully exploit their swimming ability immediately and as fast as possible in order to encounter the egg. The initial velocity is very high at activation, but motility duration lasts for periods ranging only 40 s to 20 min as an energetic consequence of the high velocity (Cosson et al 2008). As possible to see the fish spermatozoa are much different from mammalian one.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation
“…During spermatogenesis, sperm cells are prepared for accomplishing their fertilizing task for which they need to fully exploit their swimming ability immediately and as fast as possible in order to encounter the egg. The initial velocity is very high at activation, but motility duration lasts for periods ranging only 40 s to 20 min as an energetic consequence of the high velocity (Cosson et al 2008). As possible to see the fish spermatozoa are much different from mammalian one.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The fish sperm cells are homogenous; all spermatozoa can be activated at the same time and then swim with very similar characteristics at a certain time point post-activation. In many fish species, the flagellum is 50-60 mm long with a ribbon shape (presence of fins) instead of cylindrical; thus, the flagellum appears brighter by dark-field microscopy, allowing clear visualization of wave shapes (Cosson et al 2008). Just for knowledge, the head of investigated us rainbow trout spermatozoa is ovoid-shaped, measuring about 3 x 1.3 µm in diameter and possess any acrosome.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Studies in fish indicated that environmental osmotic changes trigger sperm motility [1,2]. Interestingly, in most mammalian species examined, the sperm journey from the male to female reproductive tract also experiences a natural osmotic decrease [3,4], implicating that an osmotic stress response upon ejaculation is evolutionarily conserved for normal sperm function.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm velocity represents a global combination of several parameters such as head dimension (diameter of head), beat frequency, length of flagellum and physical parameters of wave propagation like wave length and amplitude [43], which contributes differentially to energetic exhaustion. Velocities of spermatozoa are greatest immediately after activation [4], for example, in halibut 150-180 μm/s [81,82], in fugu 160 μm/s [83], in cod 65-100 μm/s [84] or 130 μm/s [64], in hake 130 μm/s [64,85], in tuna 215-230 μm/s [86], in turbot 220 μm/s [70,87] and in sea bass 120 μm/s (straight line velocity) [69,88]. High initial velocity leads to shortened total duration of motility, because fish spermatozoa mostly rely on their preaccumulated energy store for operating their propulsive motors [4,9].…”
Section: Evaluation Of Fish Sperm Motility Parametersmentioning
confidence: 99%
“…Sperm migrating in high viscosity fluids commonly exhibits larger numbers of waves though of lower amplitudes [86,107]. Thus, an increase in viscosity by addition of viscous compounds in the swimming medium actually leads to a lowering of propulsive velocity of the sperm [86].…”
Section: +mentioning
confidence: 99%